Policy Formulation Analysis of Youth Friendly City: Policy Studies of Ministry of Youth and Sports and the City Government of Bandung - Putra Dewantoro, Rizki; Fitrianti, Rachma (Journal of Strategic and Global Studies, 2021)
The planning of Youth Friendly City policy by Indonesian Ministry of Youth and Sports is expected to strengthen youth development and empowerment in each region of Indonesia, through the assistance of the preparation of youth regulation, competition, and awards. The city of Bandung has become a pilot project for Youth Friendly City. This research is an action-research approach which based on Soft System Methodology (SSM) to analyze the formulation of Youth Decent Friendly policy at the Ministry of Youth and Sports and also the City Government of Bandung. The results of this study indicate that indicators of the development of Youth Friendly City as stated in Regulation No. 11 of the Ministry of Youth and Sports 2017, refers to 4 (four) clusters, namely: life, play, work/school, and health/welfare still require more action plans. The results from this study is expected to be a reference for all city/regional government in Indonesia, especially the Government of Bandung on the policy of Youth Friendly City.